(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
This report focuses on patterns of suicide in tri-centre setting. The autopsy records from the Forensic Department of University Malaya Medical Centre (UMMC) Kuala Lumpur, Forensic Department of Hospital Kuala Lumpur (HKL) and Department of Forensic and Toxicology, University College of Medical Sciences, Delhi were analysed retrospectively.. Data was reviewed from January 2001 to December 2005. 1,866 cases were analysed with regard to age, gender, ethnicity and religion. Our study concludes that methods of committing suicide such as hanging, fall from height, poisoning, burning, cutting wrists or throat and gunshot wounds vary in magnitude at the above two centres. In UMMC fall from height (43%) was the most common method of committing suicide with most victims coming from the age group of 21- 30 yearswhereas in HKL poisoning (53%) was the most common method of committing suicide with most victims coming from the age group of 31-40 years. While, at UCMS burning (45%) was the most common method with most victims coming from the age group of 21-30 years (23%). At UCMS, suicide was slightly higher amongst females (52%) as compared to males who committed suicide, by burning one’s self/ self-immolation (33%) which was the most common method, whereas more males were involved in suicide at both UMMC (69%) and HKL (85%) with hanging (33%) and poisoning (48%) as the most prevalent methods respectively. Most of the suicide cases in UMMC (40%) and HKL (37%) involved the Chinese with hanging (16%) and poisoning (15%) as the preferred methods respectively. At UCMS, majority of victims of suicide were Hindus (82%) with burning oneself/ self-immolation (35%) as the most common method, while at HKL, majority of suicide victims belonged to Buddhists religion (37%) with poisoning (15%) as the most common method.